Atopic Dermatitis and Association of Risk for Henoch–Schönlein Purpura (IgA Vasculitis) and Renal Involvement Among Children: Results From a Population-Based Cohort Study in Taiwan. Issue 3 (January 2016) - Wei, Chang-Ching; Lin, Cheng-Li; Shen, Te-Chun; Li, Tsai-Chung; Chen, An-Chyi
Abstract : Abstract: Elevation of Th2 cytokine-driven inflammatory mediators has been reported in acute stage of Henoch–Schönlein purpura (HSP). However, the temporal interaction between Th2-mediated allergic diseases and HSP with renal involvement remains unknown. Herein, we conducted a population-based cohort analysis to investigate the risk of HSP and renal involvement in children with atopic dermatitis (AD) as 1 of the first steps in the atopic march. From 2000 to 2007, 95, 208 children with newly diagnosed AD and 190, 416 randomly selected non-AD controls were included in the study. By the end of 2008, incidences of HSP in both cohorts and the AD cohort to non-AD cohort hazard ratios (HRs) and confidence intervals (CIs) were measured. Comparison of renal involvement in HSP between children with and without AD was analyzed. The incidence of HSP during the study period was 1.75-fold greater (95% CI: 1.27–2.42) in the AD cohort than in the non-AD cohort (14.2 vs 8.11 per 100, 000 person-years). The AD to non-AD HR of HSP was greater for girls (1.92, 95% CI: 1.18–3.13), children older than 6 years (2.54, 95% CI: 1.15–5.59), and those living in less urbanized area (2.74, 95% CI: 1.10–6.82). Concurrent allergic rhinitis or asthma did not increase the HR of HSP further. The HR for HSP in AD children increased from 0.67 (95% CI: 0.41–1.11) for those with ≤2 AD-related visits to 9.77 (95% CI: 6.44–14.8) for those with >4 visits ( P  < 0.0001, by the trend test). The risk of developing HSP in the AD cohort was highest within first year after AD diagnosis (HR: 3.99; 95% CI: 1.61–9.89). AD cohort with HSP had higher occurrence rate of renal involvement, particular hematuria, than non-AD cohort with HSP. AD children had a greater risk of developing HSP and HSP with renal involvement. Further research is needed to clarify the role of allergy in the pathogenesis of HSP and renal involvement.